"إمكانية تطبيق الإدارة الالكترونية في إدارة صناعة التأمين"دراسة استطلاعية في شركة التأمين الوطنية - احمد محمد جاسم الجميلي (Journal of Madenat Alelem University College, 2018)
This research aims to stimulate insurance companies to take care of electronic management, Especially if we know that many institutions and companies do not have a clear vision in this area, So the research included a theoretical framework to define what electronic management and what are their requirements and characteristics. The Iraqi National Insurance Company has been selected as a field for the application of the research, to identify the directions and opinions of its employees and then come up with a number of proposals to contribute to the improvement and improvement of the company’s performance The research used a questionnaire form as a tool for study. The research included four hypotheses, the analytical descriptive method, and the statistical methods. The questionnaire data was analyzed, the hypotheses were tested, the results were extracted and the suggestions were submitted. The study reached a number of conclusions, including the company’s financial capabilities for electronic transformation, as well as human and technical capabilities, and the research presented a set of recommendations, The need to rely on the applications of electronic management in business organizations in general and service in particular for the advantages that stand at the forefront of achieving the satisfaction of all beneficiaries and improve the performance of these organizations.